2017
DOI: 10.4322/2176-1523.1224
|View full text |Cite
|
Sign up to set email alerts
|

Degradação Mecânica Do Coque Em Testes De Tamboreamento

Abstract: ResumoEsse estudo avaliou a resistência mecânica a frio do coque, utilizando pequenas quantidades (300 a 1200 g) desse material, como alternativa aos testes usuais que utilizam 10 e 50 kg de coque. Para isso, as degradações volumétrica e superficial foram avaliadas em um tambor de menores dimensões (Diâmetro: 268 mm, comprimento: 470 mm), bem como no tambor especificado pela norma JIS K2151 (1,5 x 1,5 m). Para o equipamento menor encontrou-se que a taxa de degradação superficial (K) aumenta ligeiramente com a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Silva (2016) [5], observed that, during transport, screening and charging of coke in the blast furnace, it exists three distinct mechanisms of fragmentation, evidenced in Figure 2. For Silva (2016) [5], even if the drum test does not accurately represent all the efforts that coke is submitted to its consumption in the blast furnace, the test must essentially reproduce the mechanisms of degradation that occurs in such fuel, considering the importance of evaluating the coke resistance to mechanical fragmentation. According to Silva (2016) [5], initially the surface degradation rate of the coke submitted to the drum is high.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva (2016) [5], observed that, during transport, screening and charging of coke in the blast furnace, it exists three distinct mechanisms of fragmentation, evidenced in Figure 2. For Silva (2016) [5], even if the drum test does not accurately represent all the efforts that coke is submitted to its consumption in the blast furnace, the test must essentially reproduce the mechanisms of degradation that occurs in such fuel, considering the importance of evaluating the coke resistance to mechanical fragmentation. According to Silva (2016) [5], initially the surface degradation rate of the coke submitted to the drum is high.…”
Section: Introductionmentioning
confidence: 99%
“…For Silva (2016) [5], even if the drum test does not accurately represent all the efforts that coke is submitted to its consumption in the blast furnace, the test must essentially reproduce the mechanisms of degradation that occurs in such fuel, considering the importance of evaluating the coke resistance to mechanical fragmentation. According to Silva (2016) [5], initially the surface degradation rate of the coke submitted to the drum is high. This rate is reduced through the progression of the test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation